2020
DOI: 10.3389/fmicb.2020.00391
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Elicits and Is Restricted by Nitric Oxide and Reactive Oxygen Species on Tomato

Abstract: The enteric pathogen Salmonella enterica can interact with parts of the plant immune system despite not being a phytopathogen. Previous transcriptomic profiling of S. enterica associating with tomato suggested that Salmonella was responding to oxidative and nitrosative stress in the plant niche. We aimed to investigate whether Salmonella was eliciting generation of reactive oxygen species (ROS) and nitric oxide (NO), two components of the microbe-associated molecular pattern (MAMP)-triggered immunity (MTI) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…The up-regulation of genes involved in dealing with oxidative and nitrosative stress conditions suggests that Salmonella must respond to these stresses to successfully colonize the plant surface. Our research group continues to investigate this interaction and recently revealed that S. Newport can, in fact, elicit the release of NO and ROS in tomato plants ( Ferelli et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The up-regulation of genes involved in dealing with oxidative and nitrosative stress conditions suggests that Salmonella must respond to these stresses to successfully colonize the plant surface. Our research group continues to investigate this interaction and recently revealed that S. Newport can, in fact, elicit the release of NO and ROS in tomato plants ( Ferelli et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the response of Salmonella ser. Newport to oxidative stress induced in tomato plants is crucial for the survival of bacteria in the plant environment ( Ferelli et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…An infected tomato leaf apoplast relieves suppression of S. enterica replication, suggesting that Xanthomonas infection aids in overcoming the host immune response and/or liberates nutrients inaccessible to S. enterica . S. enterica is known to elicit the plant immune response (52) upon recognition of microbe-associated molecular markers such as flg22 (53, 54), although some evidence suggests that the host response provoked by S. enterica is relatively weak (55, 56). If modulation of the immune response by Xanthomonas does enhance S. enterica fitness in the apoplast, it is likely that this is not the only mechanism involved.…”
Section: Discussionmentioning
confidence: 99%